2010
DOI: 10.2139/ssrn.1545291
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory Colleges: The Global Financial Crisis and Improving International Supervisory Coordination

Abstract: In a recent report, the International Monetary Fund ("IMF") encouraged the development of colleges of supervisors regulating internationally active banks and suggested that these colleges be more inclusive to avoid protectionist tendencies. Int'l Monetary Fund, Strategy, Policy & Review Dep't, Initial Lessons of the Crisis for the Global Architecture and the IMF 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…There is a long-standing debate regarding parochial competition in laxity between regulators. 5 Regardless of whether supervisors consciously pursue such competition, interagency coordination, including data sharing, should reduce incentives for "forum shopping" by entities seeking to evade regulatory interference.…”
Section: Asymmetric Information and Disclosure Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a long-standing debate regarding parochial competition in laxity between regulators. 5 Regardless of whether supervisors consciously pursue such competition, interagency coordination, including data sharing, should reduce incentives for "forum shopping" by entities seeking to evade regulatory interference.…”
Section: Asymmetric Information and Disclosure Regulationsmentioning
confidence: 99%
“…Nonetheless, formal confidentiality agreements, such as contained in Memoranda of Understanding (MoUs), among college members facilitate this process." See also Alford[5].…”
mentioning
confidence: 99%
“…This brings us to the relationship between the home banking supervisors in the country where a cross-border financial group is officially registered and host supervisors in all countries where the financial group has branches and subsidiaries. In the late 1980s, supervisory colleges were formed to oversee the activities of banks with extensive cross-border operations (Alford 2010). These colleges brought together home and host bank supervisors from diverse jurisdictions such as the Cayman Islands, France, Germany, Hong Kong, Luxembourg, Spain, Switzerland, the United Arab Emirates, the United Kingdom, and the United States.…”
Section: Domestic Levelmentioning
confidence: 99%
“…In the late 1980s, supervisory colleges were set up to oversee the activities of banks with large cross-border operations. Those colleges brought together home and host banking supervisors from diverse jurisdictions such as the Cayman Islands, France, Germany, Hong Kong, Luxembourg, Spain, Switzerland, the United Arab Emirates, the United Kingdom, and the United States (Alford 2010). Colleges met on a regular basis to discuss the supervision of a particular financial institution, identify issues or problems early on, and take actions to reduce the risk of a bailout or bank failure.…”
Section: Section 54 Home-host Supervisionmentioning
confidence: 99%
“…This solution would leave supervision at the level of the home member state, while recognising the need for other member states to take a role in the supervisory process. However, it has been suggested that there might be limitations to this type of mechanism for the coordination of supervision of cross-border financial institutions (Alford, 2010). Non-harmonised mandates and powers of financial supervisors that form part of the college could result in lack of proper leadership and failures in consolidated supervision, which would generally undermine its effectiveness (Alexander et al , 2006).…”
Section: The Case For the Introduction Of Depositary Passportmentioning
confidence: 99%